PEMENUHAN KEBUTUHAN SEKSUAL PADA JOMLO - Andan Firmansyah; Heri Ariyanto; Henri Setiawan; Suhanda Suhanda (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2021)
Introduction: According to Maslow, there are five basic human needs (KDM), namely physiological needs, comfort and security needs, love and affection needs, self-esteem needs, and self-actualization needs. One of the five most important KDM is physiological needs such as sex, this is one of the important indicators in human needs that must be met. Sexuality is a way of how to function and maintain the health of reproductive organs optimally. Objective: The purpose of this study was to find out how to fulfill the sexual needs of single people. Methods: This study uses a quantitative descriptive research with a cross sectional approach. The population in this study was an open population that met the inclusion and exclusion criteria. Respondents' inclusion criteria include; boys and girls aged 12-14 years; can write and read; and willing to fill out informed consent through the google form platform. While the respondents' exclusion criteria are; suffer from chronic diseases; being on psychotic medication; and do not have a cellphone/mobile phone/smartphone. Collecting data using a research instrument in the form of a 10-point Likert scale behavioral questionnaire. After the data was obtained, it was analyzed using IBM/SPSS software version 25.0 which was grouped into sociodemographic and behavioral categories of respondents. Behavior is declared positive if the questionnaire score <50. Results: From the study population and the overall sample based on the inclusion criteria, 154 respondents. The results showed that all respondents had positive behavior in fulfilling their sexual needs with a total score of less than 50. Conclusion: Based on the research that has been done, it can be concluded that the respondents' perceptions of sexual behavior in singles are categorized as positive, meaning good.